MR-guided adaptive versus ITV-based stereotactic body radiotherapy for hepatic metastases (MAESTRO): a randomized controlled phase II trial - Hoegen-Saßmannshausen, Philipp; Zhang, Kevin Sun; Tonndorf-Martini, Eric; Weykamp, Fabian; Regnery, Sebastian; Naumann, Patrick; Uzun-Lang, Kristin; Ristau, Jonas; Körber, Stefan A.; Dreher, Constantin; Buchele, Carolin; Rippke, Carolin; et al. (Radiation oncology, 2022)
Stereotactic body radiotherapy (SBRT) is an established local treatment method for patients with hepatic oligometastasis or oligoprogression. Liver metastases often occur in close proximity to radiosensitive organs at risk (OARs). This limits the possibility to apply sufficiently high doses needed for optimal local control. Online MR-guided radiotherapy (oMRgRT) is expected to hold potential to improve hepatic SBRT by offering superior soft-tissue contrast for enhanced target identification as well as the benefit of gating and daily real-time adaptive treatment. The MAESTRO trial therefore aims to assess the potential advantages of adaptive, gated MR-guided SBRT compared to conventional SBRT at a standard linac using an ITV (internal target volume) approach.
Gesehen am 12.06.2022